Numerical analysis of biothermal-fluids and cardiac thermal pulse of abdominal aortic aneurysm - Ng, Eddie Yin Kwee (2023)
Abdominal aortic aneurysms are serious and difficult to detect, conditions can be deadly if they rupture. In this study, the heat transfer and flow physics of Abdominal Aortic Aneurysm (AAA) were discussed and associated with cardiac cycle to illustrate the cardiac thermal pulse (CTP) of AAA. A CTP and infrared thermography (IRT) evaluation-based on AAA and abdomen skin surface detection method was proposed, respectively. Infrared thermography (IRT) is a promising imaging technique that may detect AAA quicker and cheaper than other imaging techniques (as biomarker). From CFD rigid-wall and FSI Analysis, the transient bioheat transfer effect resulted in a distinct thermal signature (circular thermal elevation) on the temperature profile of midriff skin surface, at both regular body temperature and supine position, under normal clinical temperature. However, it is important to note that thermography is not a perfect technology, and it does have some limitations, such as lack of clinical trials. There is still work to be done to improve this imaging technique and make it a more viable and accurate method for detecting abdominal aortic aneurysms. However, thermography is currently one of the most convenient technologies in this field, and it has the potential to detect abdominal aortic aneurysms earlier than other techniques. CTP, on the other hand, was used to examine the thermal physics of AAA. In CFD rigid-wall Analysis, AAA had a CTP that only responded to systolic phase at regular body temperature. In contrast, a healthy abdominal aorta displayed a CTP that responded to the full cardiac cycle, including diastolic phase at all simulated cases. Besides, the findings from FSI Analysis suggest the influence of numerical simulation techniques on the prediction of thermal physics behaviours of AAA and abdominal skin surface. Lastly, this study correlated the relationship between natural convective heat transfer coefficient with AAA and provided reference for potential clinical diagnostic using IRT in clinical implications.